Adult Education in Institutions of Vocational (Technical and Vocational) Education. Current Performance and Development Prospects - Liesnikova М. V. (Statistics of Ukraine, 2023)
The vocational (technical and vocational) education (V(TV)E) of adults constitutes an important component of the continuous lifelong learning. The article’s objective is to analyze the current performance of adult training in (P(PT)E) institutions and outline future development prospects for this component in the context of existing challenges of martial law and the postwar rebuilding of the Ukrainian infrastructure. The years of 2021 and 2022 witnessed the gradually increasing numbers of the unemployed population that were admitted to (P(PT)E) institutions for the primary professional training. Ukraine had been taking effective measures to engage adults, first and foremost unemployed ones, in V(TV)E institutions. Its legal and normative framework is the amendments in the current Law of Ukraine “Professional (Professional Technical) Education”, especially with respect to obtaining partial professional qualifications with purpose of training and retraining by short-term programs for specific needs in the country’s rebuilding. On the basis of centers for practical training, V(TV)E institutions and their social partners offer the adult population, including internally displaced persons, short-term module courses allowing one to quickly learn a profession and start working, which will help him/her quickly enter the labor market and meet the domestic economy needs in skilled staff. More than 30 types of short-term module courses for adult population are being offered in all the Ukrainian regions located at a distance from the warfare zone. The professional training in Ukraine is organized by the cluster approach, with high performing education & production clusters of industry focus, offering course training to the adult population. The existing situation can be improved, with adult population, unemployed one in particular, encouraged to train in V(TV)E institutions, though expanding public-private partnerships, especially the above-mentioned clusters. Another important step is elaborating and implementing effective actions aimed at popularization of V(TV)E among the adult population. Of the regulatory measures, the approval of new Laws of Ukraine “On Vocational and Technical Education” and “Adult Education” should be highlighted.